So many lifetimes locked inside: reflecting on the use of music and songs to enhance learning through emotional and social connection in Trainee Clinical Psychologists. Issue 3 (4th May 2018) - Keville, Saskia; Nutt, Katherine; Brunton, Isabel; Keyes, Carly; Tacconelli, Erasmo
Abstract: Music is universal; it can provide a common language that speaks from the heart enabling others to connect with the private felt experiences of others regardless of differences within or between people. This ability to empathise with, and understand, the position of others from differing backgrounds is an important competency within the therapeutic work of Clinical Psychologists. There are many facets to diversity just as there are many facets to music. Diversity in music genres can reflect diversity in people. Indeed, there is music to cater for all tastes, cultural/ethnic backgrounds, gender, age and generations with listening often being guided by individual preferences. In the United Kingdom training to become a Clinical Psychologist consists of a university-based 3-year full time professional research doctorate funded through the National Health Service. Trainees work on placements 3 days a week and attend university for academic and research teaching 2 days a week. As part of the academic programme, Trainees undertake experiential learning through workshops and methods such as Problem-Based Learning (PBL). One of the PBL exercises is based on a typical referral within an Adult Mental Health (AMH) service. For the AMH PBL exercise music is used to enhance trainees' ability to connect emotionally with the personhood of referrals, consider associated complexities, and to reflect on personal and professional boundaries and reflective practice during training and beyond. This paper reflects on the utility of music and songs to enhance the learning experience.